Kampung Aksi Membangun Pelaku UMKM dalam Pembentukan Koperasi dan Pirt di Desa Macanputih - Dian Pratama; Wulan Ruhiyyih Khanum (FEB-UP Press, 2020)
Macanputih is a village located in Kabat Subdistrict, Banyuwangi Regency, where most of its citizens work in the agricultural sector. This village is a village built by the Accounting Study Program of Airlangga University from October 2018. The problem that occurred in this village is the lack of public awareness in cultivating local potential in the village. After the first volume of community service was carried out, the other problems that arose were MSMEs and Farmers' Groups who had limitations in enlarging capital and licensing PIRTs on their products, even though the products were already well known and competitive. Seeing this problem, the Accounting Study Program of Airlangga University held a Accounting Village program, which is a sustainable community service to develop the potential possessed by Macanputih village, activities carried out in stages, ranging from training to the utilization of local potential, to economic development. Through this activity, it is expected that residents in Macanputih Village can work together with related parties in developing their villages. Another expected output is the formation of cooperatives to help with capital problems faced.